Pelatihan Pembuatan Media Poster bagi Para Mahasiswa: Poster Making Training for Students - Gunawan, Hendra; Supriyatna, Iyep Dede; Rahayu, Silvia Sri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Students are expected to excel in academic and non-academic fields in today's academic environment. One common non-academic competition is poster design. It is important to provide training to prepare students for participation in various poster competitions. This activity aims to offer practical training in poster media creation for students at Universitas 'Aisyiyah Bandung. The participants in this community service program are 23 students from Universitas 'Aisyiyah Bandung, representing different study programs and student organizations. The training method includes presentations, discussions, and hands-on assignments. The program is carried out in four stages: obtaining permissions, program socialization, activity implementation, evaluation, and post-training follow-up. The results show that students responded positively and enthusiastically, engaging in interactive discussions with the speakers. In conclusion, this community service initiative gave the students new knowledge and skills in poster media creation.